COMPARING PRICES OF BASIC NEEDS (FOODS AND HOUSES): A CASE STUDY OF CHANGLUN, KODIANG AND JITRA - Ismail, Suzilah; Wan Lee, Andrea Tan (Journal of Technology Management and Business, 2018)
Recently, the price of goods and services including the basic needs (foods and houses) in Malaysia are increasing slightly. Based on random interviews, there are complaints from low level income community of Changlun claiming that the price of basic needs especially foods and houses in Changlun are more expensive than Kodiang and Jitra. The purpose of this community based study is to investigate the claim of the low level income community whom are majority in Changlun. An observational study was conducted for 6 weeks by collecting actual prices of basic needs (foods and houses) in Changlun, Kodiang and Jitra. Exploratory Data Analysis (EDA) was used to compare the prices. The findings indicated that there exist price disparity of basic needs among Changlun, Kodiang and Jitra. Based on the samples taken, Changlun has the highest prices for foods. However, the prices were still within the price range of Kementerian Perdagangan Dalam Negeri, Koperasi dan Kepenggunaan (KPDNKK). Changlun also has the highest house price with the price disparity of RM18,000 and RM90,000 as compared to Jitra and Kodiang respectively. Further investigations needed to collect more data to generalise this issue and before actions can be taken to assist the low level income community in Changlun to cope with the price hike and survive day to day basis.Keywords: Basic needs, prices, community